Sustainability and Climate Risk Analysis of Gold as a Central Bank Reserve Asset - Dávid Marczis; Tímea Karácsony; András Straubinger (Financial and Economic Review, 2025)
Gold is a precious metal with several functions: it has been widely used in jewellery for thousands of years, and, as it serves as a store of value and has other special financial properties, it is also used as an investment asset. Gold also plays a prominent role in central bank reserves, primarily as a safe-haven asset and diversifier. Climate change may have negative social and economic consequences, such as intensifying geopolitical tensions and rising inflation, which may increase demand for safe-haven assets, including gold. Considering the role gold plays in central bank reserves, it is important to understand its climate risk profile as well. In this paper, we assess the physical and transition risks of gold investments. The main message of our analysis is that gold as a final product is practically indestructible and therefore its physical risk exposure is negligible, but its transition risk profile cannot be clearly determined.